Ultra-Widefield Retinal Optical Coherence Tomography (OCT) and Angio-OCT Using an Add-On Lens - Bartosz L. Sikorski (Diagnostics)
Purpose: This study aims to evaluate the clinical utility of a prototype ultra-widefield (UWF) single-capture optical coherence tomography (OCT) lens developed to image large areas of the retina. Material and Methods: This study included OCT and angio-OCT measurements performed with a REVO FC 130 (Optopol Technology, Poland) with an add-on widefield lens in a case series of 215 patients with retinal pathologies and 39 healthy subjects. The imaging width provided by the lens was 22 mm (covering a 110-degree field of view), while the scanning window height ranged from 2.8 to 6 mm. Results: The quality of the peripheral UWF OCT and angio-OCT images obtained by REVO FC 130 with the attachable lens is very good and sufficient for patient diagnosis, follow-up, and treatment planning. Both the boundaries of the non-perfusion zones and the location and extent of vascular proliferations can be accurately traced. Furthermore, the vitreoretinal interface can also be accurately assessed over a large area. The imaging quality of the macula with UWF OCT angiography is also good. The mean thickness measurement difference between a UWF and a standard 10 mm 3D retinal scan in a healthy individuals for the Central ETDRS sector was −1.37 ± 2.96 µm (the 95% limits of agreement (LoA) on Bland–Altman plots ranged from −6.82 to 2.43); for the Inferior Inner sector, it was −2.81 ± 1.09 µm (95% LoA, −4.94 to −0.68); for the Inferior Outer sector, it was −1.31 ± 2.58 µm (95% LoA, −6.38 to 3.75); for the Nasal Inner sector: −1.46 ± 1.19 µm (95% LoA, −3.79 to 0.88); for the Nasal Outer sector, it was −0.56 ± 2.61 µm (95% LoA, −5.67 to 4.55); for the Superior Inner sector, it was −2.71 ± 3.16 µm (95% LoA, −8.91 to 3.48); for the Superior Outer sector, it was −1.82 ± 1.39 µm (95% LoA, −4.55 to 0.91); for the Temporal Inner sector, it was −1.77 ± 2.24 µm (95% LoA, −6.16 to 2.62); for the Temporal Outer sector, it was −3.61 ± 1.43 µm (95% LoA, −6.41 to −0.81). Discussion: The proposed method of obtaining UWF OCT and UWF angio-OCT images using an add-on lens with the REVO FC 130 gives high-quality scans over the entire 110-degree field of view. This study also shows a high agreement of the ETDRS sector’s thickness measurements between UWF and standard retinal scans, which allows UWF to be used for quantitative macular thickness analysis. Considering its image quality, simplicity, and reliability, an add-on lens can be successfully used for the UWF OCT and OCT angiography evaluation of the retina on a daily basis.